PENGEMBANGAN POTENSI EKONOMI KAWASAN PESISIR DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - Eva Santi Santi Anah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2017)
Indonesian coastal areas have enormous potential to be developed in improving the welfare of the community, considering that there are still many underprivileged people, and almost 62% of the total population is categorized as living below the poverty line and developing local potentials in the coastal areas requires development. One of the potentials is in the seaweed sector and tourism. Therefore, the next one is developed based on the concept of local economic development. This literature review summarizes the stages or processes for developing coastal economic potential, as well as managing coastal economic potential which includes: Economic Development of Coastal Communities with Seaweed Business in Jumiang Coast, and Development of Marine Tourism Destinations in Buleleng Regency.